2010
DOI: 10.1002/app.32711
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of nanocomposite barrier film containing encapsulated nanoclay

Abstract: Waterborne poly(styrene-co-butyl acrylate) was prepared via miniemulsion polymerization in which nanoclay (Cloisite V R 30B, modified natural MMT) in different concentrations was encapsulated. Scanning electron microscopy, X-ray diffraction, and transmission electron microscopy confirmed the encapsulation and intercalatedexfoliated structure of Cloisite V R 30B within poly(styrene-cobutyl acrylate). The effect of nanoclay content on water vapor permeability, water uptake, oxygen permeability, thermal, and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…They identied that improved barrier properties of the polymer/clay nanocomposites was primarily due to an increase in the degree of crystallinity of the polymer. 175 They found that the gas barrier properties of NR composites with SMK and precipitated silica were much higher than those of NR/ precipitated silica composites and NR/SMK.…”
Section: Gas Barrier Properties Of Polymer/ Clay Nanocompositesmentioning
confidence: 99%
“…They identied that improved barrier properties of the polymer/clay nanocomposites was primarily due to an increase in the degree of crystallinity of the polymer. 175 They found that the gas barrier properties of NR composites with SMK and precipitated silica were much higher than those of NR/ precipitated silica composites and NR/SMK.…”
Section: Gas Barrier Properties Of Polymer/ Clay Nanocompositesmentioning
confidence: 99%
“…Past research has shown that there is a direct linkage between properties of nanocomposites and quality of nanoclay dispersion [52][53][54][55][56][57]. In fact, the extent of improvement, as result of adding nanoclay, cannot be solely proportional to nanoclay loading because of difficulty in obtaining good dispersion at high loading.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…As in polymer–polymer core shell particle formation, the interplay of thermodynamic and kinetic factors is also operating in clay encapsulation through (mini)emulsion polymerization. Looking from the starting point of miniemulsion polymerization, thermodynamically the clay has to be modified hydrophobically to make it miscible with the monomer initially . But the interfacial tensions change during the polymerization and the resulting morphology can still be armored latex particles.…”
Section: Resultsmentioning
confidence: 99%
“…Looking from the starting point of miniemulsion polymerization, thermodynamically the clay has to be modified hydrophobically to make it miscible with the monomer initially. [12][13][14][15][16][17][24][25][26][27][28][29][30][31] But the interfacial tensions change during the polymerization and the resulting morphology can still be armored latex particles. An interesting example is given by Chakrabary and Singha [25] where the use of neutral functional monomer, in combination with a fluorinated acrylate in miniemulsion polymerization, led to encapsulated Cloisite hybrid latex particles (multiple clay platelets per particle) whereas the use of a positively charged functional monomer led to armored morphology.…”
Section: Interplay Of Kinetic and Thermodynamic Factors In Clay Encapmentioning
confidence: 99%
See 1 more Smart Citation